PENERAPAN TEKNIK PEMBELAJARAN RODA KEBERUNTUNGAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 11 PADANG - Meylia Rahman, Shinta; Febriana, Rina; Melisa, Melisa (STKIP PGRI Sumbar, 2014)
ABSTRACTThis study was motivated by an understanding of mathematical concepts class VII students of SMP Negeri 11 Padang is still low , and the learning of mathematics is difficult and tedious . This study aims to determine whether students understanding of mathematical concepts using learning techniques wheel of chance better than studentâs understanding of mathematical concepts by applying Â conventional learning in the classroom SMP Negeri 11 Padang. This research is an experimental study with randomized research design of the subject. The instrument used was the final test. From of the best used is the essay with reliability = 0,8988. The result obtained from testing the hypothesis t = 2,32 and t table = 1,699, t count > t table then hypothesis is accepted. It can be concluded that the students understanding of mathematical concepts Â by applying using techniques that wheel of fortune better than the mathematical ability of students understanding of concepts with conventional learning in the classroom SMP Negeri 11 Padang.